Five minds for the future - Gardner, Howard (Boston : Harvard Business School Press, 2007)
Discusses five cognitive abilities--synthesis, creativity, respect, ethics, and mastery of major schools of thought and a professional craft--that will grow in importance in school, business, and other settings with globalization, increased information transfer, and other shifts and changes in the world.
Minds viewed globally: a personal introduction -- The disciplined mind -- The synthesizing mind -- The creating mind -- The respectful mind -- The ethical mind -- Conclusion: toward the cultivation of the five minds.
Includes bibliographical references (p. 169-173) and index.
Pub Weekly.
Adult
Keywords: Multiple intelligences; Social intelligence; Success; Thought and thinking; Multiple intelligences; Social psychology; Success; Thought and thinking